The Impact of Climate Change on Biblical Interpretation and Theology - Richard Osei Akoto (E-Journal of Humanities, Arts and Social Sciences)
This study investigates how climate change influences biblical interpretation and theology, with the aim of aligning ecological concerns with scriptural and doctrinal perspectives. Key goals include examining reinterpretations of scripture, assessing the ethical and theological dimensions of ecological crises, and evaluating denominational responses. Using a qualitative, interdisciplinary approach, the study incorporates literature review, ecological hermeneutics, and theological reflection to explore how environmental issues reshape core biblical themes and doctrines. Engaging scholars like Jürgen Moltmann, Sallie McFague, Richard Bauckham, and Pope Francis, it analyzes eco-theological insights on creation, stewardship, sin, redemption, and eschatology. The findings suggest that climate change compels a renewed focus on stewardship, reimagines eschatology with ecological justice, and inspires churches to integrate climate action into doctrine and practice. The study recommends educational initiatives in churches, ecological integration in theological training, and advocacy by faith leaders for sustainable policies—contributing a framework that brings ecological awareness into theological discourse.